Accounting Based Determinants of Stock Prices in LQ45 IDX Firms - Fitri Dwi Jayanti; Arda Raditya Tantra; Bulan Karima Nurani (Politeknik Ganesha Medan, 2026)
Stock prices reflect the market’s assessment of a company’s value and are influenced by fundamental factors, including capital structure, firm size, and profitability. The LQ45 Index represents companies with high liquidity and large market capitalization on the Indonesia Stock Exchange (IDX), making it important to understand the determinants of stock prices during the post-COVID-19 recovery period (2020–2024). This study aims to analyze the effect of the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), firm size (SIZE), and Return on Assets (ROA) on the stock prices of LQ45 companies listed on the IDX during 2020–2024. Using a quantitative approach with panel data regression and a fixed effect model, the sample consists of 29 LQ45 companies consistently listed during the study period, yielding 145 firm-year observations. Data were obtained from annual financial reports and analyzed using EViews 13. The results indicate that DER has a positive but insignificant effect on stock prices (? = 0.457, p = 0.0539), DAR has a significantly negative effect (? = –8.235, p = 0.0188), while SIZE (? = 1.568, p = 0.0001) and ROA (? = 45.679, p = 0.0000) both have significantly positive effects. Profitability (ROA) is identified as the most dominant determinant of LQ45 companies’ stock prices, followed by firm size and capital structure (DAR). This study has theoretical implications for strengthening capital market research and opens opportunities for future studies to incorporate new variables, expand the temporal scope, or compare different stock indices to generate more comprehensive insights. Moreover, these findings provide valuable insights for investors and corporate management regarding the factors driving stock valuation in Indonesia’s premier equity index during the post-pandemic era.